Effects of management practices on growth rate of pine plantations in Nepal - Dangal, S. P.; Das, A. K. (Banko Janakari, 2015)
With the large scale plantation commenced in the early 1980s, nearly 370,000 hectares of plantations have been successfully established in Nepal. Pinus patula is one of the dominant species of these plantations aiming to maximize biomass productions in degraded hills. The growth rate of 15 m³ ha-1yr-1 estimated in 1995 was reduced to 7 m³ ha-1yr-1 in 2011. As it is an exotic species to Nepal, the effect of management practices on its growth was not clear because of specific ecologic condition which is hindering in developing a management plan with a high confidence. Dendrocronological assessment taking sample cores of 120 trees was conducted in plantations age between 1975 and 1990. The study found that the growth rate decreased after 10 years and the rate was high in the higher density class. The cumulative increment, which was found to be higher in the lower density class, was found to have retarded faster after 15-17 years of age in the higher density class as well as in the informally managed plantations. The study recommends conducting planned thinning from the early age of 8-10 years while the final felling is recommended to be executed at the age of 30-35 years for maximizing its volume. However, a vast area of the current stock, which has already crossed or nearly crossed the rotation age of this species, should be removed in two phases ensuring the establishment of the new crops. They should be clear felled when they reach the age of 45 years. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 30-38